Droplet pairs electrical computations using a level set based algorithm - Garzon, M.; Sethian, J.A. (Journal of electrostatics, 2020)
Droplet pairs interact when exposed to electric fields, being crucial parameters in this process the initial droplet separations and the electric field intensity. We present an algorithm for the evolution of perfectly conducting and non-viscous fluids using a level set technique. Topological changes of the free boundary are automatically included in the formulation and passing through singular times is computationally possible. Numerical results on electro-hydrodynamic droplet pairs reveal three different types of droplets evolution: droplets do not coalesce, droplets coalesce, and droplets recoil after contact failing to coalesce. A comparison of numerical results with laboratory experiments is also addressed. •A robust mathematical model and algorithm for electro-hydrodynamic computations is presented.•The level set method techniques allows for computing through singular mathematical events such as drop breaking or merging.•The repulsion mode in the electric coalescence of droplet pairs observed in laboratory experiments is captured by this model.